Student loyalty through perceived service quality and satisfaction - Saoud, Souad; Sanséau, Pierre-Yves (Advances in Social Sciences Research Journal, 2019)
Student loyalty has become an important determinant of the success of Universities aiming to retain students and attract them back for post-graduate studies. To explain how student loyalty could be generated by examining the sequence of constructs: student perceived service quality, student satisfaction, and student loyalty and to identify the crucial determinants of student perceived service quality, we hypothesize that satisfaction plays an important role in linking service quality to loyalty. Using a sample of 177 students enrolled in a Lebanese University, our empirical study examines the relationship among student perceived service quality, student satisfaction, and student loyalty and identifies the important determinants of student perceived service quality. Our findings suggest that students must be satisfied with the service quality to demonstrate loyalty to their educational institution. The findings also conclude that the quality of curriculum is the most important determinant of student perceived service quality.